2014
DOI: 10.46743/2160-3715/2011.1085
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility between Text Mining and Qualitative Research in the Perspectives of Grounded Theory, Content Analysis, and Reliability

Abstract: The objective of this article is to illustrate that text mining and qualitative research are epistemologically compatible. First, like many qualitative research approaches, such as grounded theory, text mining encourages open-mindedness and discourages preconceptions. Contrary to the popular belief that text mining is a linear and fully automated procedure, the text miner might add, delete, and revise the initial categories in an iterative fashion. Second, text mining is similar to content analysis, which also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 61 publications
0
46
0
Order By: Relevance
“…Furthermore, numerous researchers have applied text mining to qualitative research projects and see text exploitation as a feasible qualitative research method (Rajman & Besançon, 1998;Camillo et al, 2005;Hong, 2009;Janasik et al, 2009;Yu et al, 2011;Mahmoudi & Abbasalizadeh, 2019;Tian et al, 2019;Wang et al, 2020). According to Rose & Lennerholt (2017), advances in text mining accompany with the widespread adoption of information technology has granted wider access to large amounts of text documents as well as automated analysis techniques.…”
Section: Text Mining and Data Clustering Methodsmentioning
confidence: 99%
“…Furthermore, numerous researchers have applied text mining to qualitative research projects and see text exploitation as a feasible qualitative research method (Rajman & Besançon, 1998;Camillo et al, 2005;Hong, 2009;Janasik et al, 2009;Yu et al, 2011;Mahmoudi & Abbasalizadeh, 2019;Tian et al, 2019;Wang et al, 2020). According to Rose & Lennerholt (2017), advances in text mining accompany with the widespread adoption of information technology has granted wider access to large amounts of text documents as well as automated analysis techniques.…”
Section: Text Mining and Data Clustering Methodsmentioning
confidence: 99%
“…From the tag clouds obtained, the final analysis of this research was carried out by estimating the meaning of the most relevant terms highlighted by LSA, evidenced in these tag clouds, along with the content analysis to emphasize the meaning of the messages analyzed in the literature. This is because text mining techniques are closely related to content analysis, which extracts data-driven categories for analysis, allowing one technique to complement the other in the process (Yu, Jannasch-Pennell, & Digangi, 2011). Four data- Disruptive business models driven categories were identified in our analysis: Disruptive technology and innovation; value proposition to consumers; maintenance of existing business models; and pattern within DBM.…”
Section: Methodsmentioning
confidence: 99%
“…Given the recent increase in prevalence and use of data analysis software applications, text-mining methods have been increasingly used as research tools to extract meaningful keywords from bulk data to answer research inquiries. Text mining provides an efficient method of identifying pairs of words that are frequently adjacent within reviews, but the extent to which the relationship of keywords is meaningful in any given context has been questioned (Feldman et al , 1998; Yu et al , 2011). The pilot test found that counting the frequency that the word “wine” appears in a review can provide only a limited understanding of the application of wine in hotels.…”
Section: Methodsmentioning
confidence: 99%